Implementasi Game Pengenalan Binatang di TK Putra I Bandung - Miftahuddin, Yusup; Kristiana, Lisa; Anindia, Hana Nathania; Sugiharto, Ariq Bagus; Adli, Muhammad Arkan; Nurrahmayanti, Fadhilah; Setiyawati, Setiyawati (Society : Jurnal Pengabdian Masyarakat, 2025)
The animal recognition game application is designed to support interactive learning at TK Putra 1 Bandung, Arcamanik District, Bandung City. This application aims to provide an engaging learning experience where young children can learn about various animals, their habitats, sounds, and distinctive features. Interactive elements such as animal images, sounds, and videos are presented in an enjoyable way, allowing children to learn in an engaging and active manner. Features such as quizzes, clickable buttons, and animations support children’s engagement, enhance curiosity, and encourage active participation in the learning process. The application is also designed to make it easier for teachers and staff to deliver interactive content, ensuring that learning takes place in an enjoyable and effective manner.